Pengaruh Strategi Pemasaran Digital dan Daya Tarik Konsumen Terhadap Keputusan Mahasiswa dalam Membeli Produk Pakaian di Universitas Dinamika Bangsa Jambi - Einike Jesika Triana; Viony Septhelim; Nadia Desfira; Ressy Allya Susanto; Yossinomita Yossinomita (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to investigate the impact of social media advertising on clothing choices at Universitas Dinamika Bangsa Jambi students. In today's world, where many people, especially young people who frequently shop online, often struggle to accurately determine the quality of items. A quantitative approach was employed, with a survey as the primary method of data collection. A questionnaire was distributed online via Google Forms and successfully elicited responses from 102 active students who are also social media users. The sampling technique used was purposive sampling, with participants selected based on criteria that matched the focus of the study. The data were then processed using SmartPLS 4 software with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to test the relationship between variables. The main findings indicate that social media promotions have a strong positive influence on students' clothing purchasing decisions. This underscores the crucial role of targeted advertising strategies in the digital world in shaping consumer preferences. This research is expected to serve as a guide for clothing entrepreneurs in developing online marketing plans that better suit the tastes and needs of students as their target market.